Implementasi Peraturan Pemerintah Nomor 94 Tahun 2021 tentang Disiplin Pegawai Negeri Sipil (Studi di Mahkamah Syariah Meulaboh) - Andre Ramadhan; Rachmatika Lestari (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
Civil Servants as employees of the State Civil Apparatus are obliged to maintain the unity and integrity of the nation, to be loyal and obedient to Pancasila and the 1945 Constitution of the Republic of Indonesia. With regard to discipline, Government Employees have issued Regulations governing discipline for Civil Servants, namely Government Regulations Number 94 of 2021 states that every Civil Servant is required to come to work and comply with the provisions on working hours, but in reality there are still violations committed by Civil Servants against the provisions for entering work. The method used in this study is Juridical Empirical with a Case Study approach, namely investigating and understanding an event. This research was conducted at the Meulaboh Sharia Court Office and the selection of informants was carried out by purposive sampling with a total of 2 informants consisting of the Chief Justice of the Meulaboh Sharia Court and 1 Head of Personnel Subdivision who would be asked for information. Data collection techniques in this study are observation, interviews and documentation. The results of the study found that there were still employees who were late for work and efforts to impose sanctions had been carried out by the Head and Head of Personnel Subdivision, including giving verbal warnings and written warnings and reducing work performance for promotion to rank. whereas light disciplinary punishment is like a violation of the obligations regulated in Article 8 number 9 which states that a violation of the obligation to come to work and comply with the provisions of working hours. Suggestions to Meulaboh Sharia Court employees to be able to carry out their duties and responsibilities and to the leaders or superiors of the Meulaboh Sharia Court to pay more attention to the performance of their employees.